ARDUINO-BASED HUMAN SENSOR FAN ASSEMBLY AIMED TO SAVE ENERGY - M. Afnan Fadilah; Gilang Ramadhan, Kholid Darwinto, Paduloh (CV. ADIBA AISHA AMIRA, 2024)
This research aims to develop an Arduino-based fan with a motion sensor that can detect the presence of people around it. Fans are often used to provide thermal comfort, but fans often work continuously without considering the presence of people in the room, resulting in wasted energy. In this research, an occupancy sensor is used to detect the presence of a person near the fan, and Arduino controls the fan speed based on this data. Experimental methods are used to test system performance that optimizes energy consumption and provides comfort to users. The research results show that an Arduino-based fan with an occupancy sensor can significantly reduce energy consumption and improve user experience by providing a fan that operates automatically based on demand. This research has the potential to reduce environmental impacts and energy costs while providing a solution for using fans that are more efficient and comfortable.